"Irrelevant" WHO outpaced by younger rivals. (9th August 2011) - Hawkes, Nigel
Abstract : The World Health Organization's critics accuse it of being bogged down in red tape and internal politics. However, attempts at reform are raising concerns over conflicts of interest. Nigel Hawkes reports